THE INFLUENCE OF ATMOSPHERE, ONLINE REVIEWS AND CUSTOMER VALUE ON REPURCHASE INTENTION - Dwini, Sekar (Lembaga Riset dan Pengabdian Masyarakat (LRPM) Institut Bisnis Nusantara, 2024)
This study aims to determine the effect of atmosphere, online review and customer valueon repurchase intention at Kina Cafe & Bar. The sampling technique used is accidentalsampling with a total of 250 respondents. Data analysis method using SEM (StructuralEquation Model) with SmartPLS software. The research results show that the atmosphereat Kina Cafe & Bar does not have a significant influence on repurchase intentions, indicatingthat the atmospheric elements at Kina Cafe & Bar are not the main factors influencingcustomers' decisions to shop there again. In contrast, online reviews have a significantinfluence on repurchase intentions indicating that customers' online reviews can be animportant component in determining customers' repurchase intentions. Apart from that,consumer values are also proven to have a big influence on the desire to repurchase. Thisshows that consumers who feel they get good value from goods or services at Kina Cafe &Bar are more likely to buy again. In this way, Kina Cafe & Bar management can concentrateon continuing to sell goods and services.